2014
DOI: 10.1557/jmr.2014.367
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanical properties and tensile fracture of Ti–Al–V alloy strip under electropulsing-induced phase change

Abstract: The effect of high-energy electropulsing treatment (EPT) on the microstructure evolution, mechanical properties, and fracture behavior of as-treated Ti-6Al-4V alloy strips was investigated. EPT was found to accelerate phase transition and microstructure evolution of quasi-single-phase titanium alloy strips at a relatively low temperature, and obtain characteristic duplex microstructure and Widmanstatten microstructure. The EPT-induced microstructural changes increased elongation-to-failure remarkably with a sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…In the substrate zone ( Figure 7 a), the intensity of the highest diffraction peak experienced alterations, along with a decrease in some peak intensities of the Ti-α phase. This is mainly attributed to the reduction of temperature at the α-phase to β-phase transition caused by the pulsed-current-induced “electron wind” effect, promoting the phase transition from α-phase to β-phase [ 29 , 30 ]. Increasing the intensity of the pulsed current enhances this effect, leading to a greater proportion of the β-phase.…”
Section: Resultsmentioning
confidence: 99%
“…In the substrate zone ( Figure 7 a), the intensity of the highest diffraction peak experienced alterations, along with a decrease in some peak intensities of the Ti-α phase. This is mainly attributed to the reduction of temperature at the α-phase to β-phase transition caused by the pulsed-current-induced “electron wind” effect, promoting the phase transition from α-phase to β-phase [ 29 , 30 ]. Increasing the intensity of the pulsed current enhances this effect, leading to a greater proportion of the β-phase.…”
Section: Resultsmentioning
confidence: 99%
“…This type of kernels appears mostly in fractional calculus [32]. Wu [33] extended Tatar's result to the equation…”
Section: + ≤ ∀ ≥ G S H G S Smentioning
confidence: 91%
“…Some studies showed that the phase transformation of the metal matrix can be facilitated and the phase transition temperature can be reduced by pulse current. In general, the conversion temperature of α→β precipitation for Ti-6Al-4 V alloy is about 676 °C [112]. Nevertheless, α phase of the Ti alloy is gradually transformed into β phase under the action of pulse current.…”
Section: Phase Transitionmentioning
confidence: 99%